Identifikasi Formalin Pada Buah Anggur (Vitis Vinifera) Di Pasar Tradisional Kabupaten Rokan Hulu - Eka Rezky Syahputra; Al Muzafri; Edward Bahar (CV. Ulil Albab Corp, 2022)
Wine has such good nutritional value asvitamins, minerals, cabohydrates, and phytopicalsubstances, a well as antioxidant, anticancet,antiinflammatory, antiaging, and antimicrobes, thefruit quickly decays this state makes the seller addpreservative material such as formaldehyde bysmearing it, injecting it, spraying it, even soaking itin a solution of formalidehyde. Formalidehyde is oneof the preservatives that have a good ability topreserve. The purpose of this to knoe whether there isor not formaldehey on red grapes sold at the marketof the municipality of rokoan hulu. The locaion forthe production of red wine is a few of the markets ofthe 8 seedilings, kunto darussalam, bangun purba,tambusai, kabun, kepnuhan hulu, rambah hilir, ujungbatu, pagaran tapah darussalam. The test resultswere described by viewing data of the test results inthe laboratory.qualitative data testing methodes aredescribed to test hypothetical research. The results ofthis study indicate that all 16 samples of red winetested were positive (+) for formaldehyde, which wasconfirmeed by testing hsil for a purple discolorationof red wine.